Ownership Structure and Its Impact on Dividend Policy: A Case of Non–Financial Companies in Pakistan - ABDUL LATIF; MUHAMMAD TAHIR KHAN; MUHAMMAD NISAR KHAN (Journal of Business & Tourism, 2021)
This article focus on one of important corporate decision that can have a great impact on the sentiments of the investor’s i.e. corporate dividend policy. This study investigates the determinants of the corporate dividend policy in the context of agency relation. The analysis of the study has based on the random sample of eighty firms from the listed companies in Pakistan, for the period of eight years ranging from 2003 to 2012. Stepwise multiple regressions have used to investigate for the relationship of ownership variables with the dividend payouts. The empirical results suggested that there has a negative relationship between the dividend payouts and managerial share ownership and thus these are alternative tools that can be used to minimize the agency problem. And also where there has positive relationship between the institutional suggested that the higher has their shareholdings the higher will be the firm dividend payouts that will leads to less availability of the cash flows with the opportunities managers to expropriate the shareholders wealth.